Clinical value of carcinoembryonic antigen in mammary neoplasms of bitches - Senhorello, Igor L. S. [UNESP]; Terra, Erika M.; Sueiro, Felipe A. R.; Firmo, Bruna F. [UNESP]; Anai, Leticia A. [UNESP]; Goloni, Camila [UNESP]; Canavari, Isabela C. [UNESP]; Ampuero, Roberto A. N. [UNESP]; Pereira, Rodrigo S.; Tinucci-Costa, Mirela [UNESP] (Wiley, 2020)
This study aimed at evaluating the behaviour and understanding the diagnostic value of the carcinoembryonic antigen (CEA) in bitches with mammary carcinoma as a tool for monitoring and prognosis of canine cancer patients. Serum samples from 77 bitches were divided into four groups, G1 (n = 21), control group (healthy/neoplasia free bitches); G2 (n = 31), bitches with non-metastatic mammary carcinoma less than 3 cm; G3 (n = 12), bitches with non-metastatic mammary carcinoma greater than 3 cm; and, G4 (n = 13) bitches with mammary carcinoma and lymph node metastasis. The marker was dosed once in G1, whereas in G2, G3 and G4, CEA levels were determined before (M0) and 15 days after (M1) mastectomy, using the ELISA kit for humans while reading used ELISYS ONE human. A group of 11 bitches was followed up 45 days after mastectomy (M2). The results for the concentration of markers in blood serum samples at the evaluated times and their relationship with neoplasia biological behaviour and observed clinicopathological changes were evaluated by the Tukey test at 5% significance. The ROC curve was established to find the cut-off value and calculate the test sensitivity and specificity, the multivariate matching analysis was performed to confirm the association between CEA values and clinicopathological variables. CEA values increased significantly in bitches with mammary carcinoma, metastatic tumours with a diameter larger than 3.0 cm and high grade, compared with healthy ones. In addition, mastectomy reduced the CEA concentration in the blood (P <.05) whereas high CEA levels were associated with unfavourable prognostic factors (P <.05). The biomarker presented good diagnostic value, especially for more aggressive tumours. In conclusion, CEA serum concentrations allowed to follow efficiently the evolution of mammary tumours in bitches, since CEA values increased in bitches with mammary gland tumour and decreased after mastectomy while correlating with prognostic factors such as tumour size, nodal metastasis and histological grade. Further studies are still needed to confirm its diagnostic value for follow-up of relapse and early metastasis.
Keywords: biomarkers; canine mammary tumour; CEA; metastasis; prognosis